Challenges and opportunities in the use of ponds and pondscapes as Nature-based Solutions - M. Cuenca-Cambronero; M. Blicharska; J.-A. Perrin; T. A. Davidson; B. Oertli; M. Lago; M. Beklioglu; M. Meerhoff; M. Arim; J. Teixeira; L. De Meester; J. Biggs; et al. (Hydrobiologia, 2023)
Ponds and “pondscapes” (networks of ponds) are crucial habitats for biodiversity and for delivering multiple benefits to humans, so-called “Nature’s Contribution to People”, such as climate mitigation and adaptation to climate change, creation, and maintenance of habitat for biodiversity, water purification, flood mitigation and cultural benefits (e.g., recreational possibilities). However, ponds are not often considered as Nature-based Solutions to provide all these benefits. In addition, there is insufficient knowledge on how to manage and restore ponds to maximise their role to increase the resilience of ecosystems and society to climate change. To facilitate improved implementation of ponds as Nature-based Solutions for the delivery of a wide range of Nature Contributions to People, it is important to generate and integrate biodiversity, ecosystems, societal, economic and policy knowledge. Hence, there is a need for evidence-based guidance to support the broader use of ponds. Here, we review the role of ponds and pondscapes in delivering Nature’s Contributions to People and provide an overview of the challenges and opportunities for their broader implementation as Nature-based Solutions. Finally, we propose a conceptual framework that can help the implementation of pond Nature-based Solutions, and that outlines future research needs.

Restoration of the eutrophic Lake Eymir, Turkey, by biomanipulation after a major external nutrient control I - M. Beklioglu; O. Ince; I. Tuzun (Hydrobiologia, 2003)

Rapid recovery of a shallow hypertrophic lake following sewage effluent diversion: lack of chemical resilience - M. Beklioglu; L. Carvalho; B. Moss (Hydrobiologia, 1999)